The risk of infection in patients with multiple sclerosis treated with disease-modifying therapies: A Delphi consensus statement - Moiola, Lucia; Barcella, Valeria; Benatti, Simone; Capobianco, Marco; Capra, Ruggero; Cinque, Paola; Comi, Giancarlo; Fasolo, Maria Michela; Franzetti, Fabio; Galli, Massimo; Gerevini, Simonetta; Meroni, Luca; et al. (Multiple sclerosis, 2021)
The risk of infection associated with immunomodulatory or immunosuppressive disease-modifying drugs (DMDs) in patients with multiple sclerosis (MS) has been increasingly addressed in recent scientific literature. A modified Delphi consensus process was conducted to develop clinically relevant, evidence-based recommendations to assist physicians with decision-making in relation to the risks of a wide range of infections associated with different DMDs in patients with MS. The current consensus statements, developed by a panel of experts (neurologists, infectious disease specialists, a gynaecologist and a neuroradiologist), address the risk of iatrogenic infections (opportunistic infections, including herpes and cryptococcal infections, candidiasis and listeria; progressive multifocal leukoencephalopathy; human papillomavirus and urinary tract infections; respiratory tract infections and tuberculosis; hepatitis and gastrointestinal infections) in patients with MS treated with different DMDs, as well as prevention strategies and surveillance strategies for the early identification of infections. In the discussion, more recent data emerged in the literature were taken into consideration. Recommended risk reduction and management strategies for infections include screening at diagnosis and before starting a new DMD, prophylaxis where appropriate, monitoring and early diagnosis.